A Medico-legal Analysis of Autopsy Cases Due to Poisoning - Nadia Aslam, Memoona Naz, Muhammad Qasim Ahmed Khan Memon, Pardeep Kumar, Abrar Ul Hasnain Memon, Ejaz Ahmed Awan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The prevalence of poisoning has increased, costing many valuable lives, as has the progress in research and technology, agriculture, and the industrial sector. Chemicals created to safeguard agricultural products from pests and rodents helped preserve the environment. People who are starving are becoming a threat to other people’s lives. Objective: This research aims to assess the frequency and pattern of poisoning. Design: Retrospective Study. Setting: Peoples Medical College Hospital in Nawabshah, Shaheed Benazirabad, Sindh. Duration: From May 1, 2021, to May 30, 2022. Methodology: The current study was conducted in the past. All suspected poisoning deaths that were presented to Peoples Medical College Hospital in Nawabshah, Shaheed Benazirabad, Sindh for a medical-legal autopsy within the course of a year, from May 1, 2021, to May 30, 2022, would be investigated. Inquest reports, hospital records, autopsy reports, and chemical examiner’s analysis reports of viscera and bodily fluids were used to compile information on suspected poisoning instances. Age, sex, religion, place of residence, marital status, education, occupation, financial situation, mental state, date and conditions of poisoning, location of treatment, and the most prevalent agent responsible for deadly poisoning are among the different epidemiological data that are examined. Conclusion: Poisoning is predicted to decline as a result of measures to enhance socioeconomic conditions through changes in employment, health care, education, and economic as well as scientific assistance for farmers. It is anticipated that proper education of the general public and farmers regarding the storage, handling, and usage of pesticides and insects will lower the frequency of poisoning. Keywords: Poisoning, Suicide, Medico-legal